Ecological specialization is associated with genetic structure in the ant-associated butterfly family Lycaenidae. Issue 1886 (12th September 2018) - Schär, Sämi; Eastwood, Rodney; Arnaldi, Kimberly G.; Talavera, Gerard; Kaliszewska, Zofia A.; Boyle, John H.; Espeland, Marianne; Nash, David R.; Vila, Roger; Pierce, Naomi E.
Abstract : The role of specialization in diversification can be explored along two geological axes in the butterfly family Lycaenidae. In addition to variation in host-plant specialization normally exhibited by butterflies, the caterpillars of most Lycaenidae have symbioses with ants ranging from no interactions through to obligate and specific associations, increasing niche dimensionality in ant-associated taxa. Based on mitochondrial sequences from 8282 specimens from 967 species and 249 genera, we show that the degree of ecological specialization of lycaenid species is positively correlated with genetic divergence, haplotype diversity and an increase in isolation by distance. Nucleotide substitution rate is higher in carnivorous than phytophagous lycaenids. The effects documented here for both micro- and macroevolutionary processes could result from increased spatial segregation as a consequence of reduced connectivity in specialists, niche-based divergence or a combination of both. They could also provide an explanation for the extraordinary diversity of the Lycaenidae and, more generally, for diversity in groups of organisms with similar multi-dimensional ecological specialization.